Impaired Development of Neural‐Crest Cell‐Derived Organs and Intellectual Disability Caused by MED13L Haploinsufficiency. Issue 11 (23rd September 2014) - Utami, Kagistia Hana; Winata, Cecilia Lanny; Hillmer, Axel M.; Aksoy, Irene; Long, Hoang Truong; Liany, Herty; Chew, Elaine G. Y.; Mathavan, Sinnakaruppan; Tay, Stacey K. H.; Korzh, Vladimir; Sarda, Pierre; Davila, Sonia; et al.
<x xml:space="preserve">Abstract</x> Several reports have identified structural variants and mutations affecting MED13L in patients with heart defects, craniofacial anomalies, and intellectual disability. In this study we functionally demonstrated that depletion of its orthologue in zebrafish model could recapitulate the craniofacial abnormalities in human and the observed phenotype can be reversed by introducing intact human mRNA, suggesting that gene dosage is required for normal gene function. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>